Virulence Factors and Pathogenicity Mechanisms of Acinetobacter baumannii in Respiratory Infectious Diseases - Yake Yao; Qi Chen; Hua Zhou (Antibiotics, 2023)
Acinetobacter baumannii (A. baumannii) has become a notorious pathogen causing nosocomial and community-acquired infections, especially ventilator-associated pneumonia. This opportunistic pathogen is found to possess powerful genomic plasticity and numerous virulence factors that facilitate its success in the infectious process. Although the interactions between A. baumannii and the pulmonary epitheliums have been extensively studied, a complete and specific description of its overall pathogenic process is lacking. In this review, we summarize the current knowledge of the antibiotic resistance and virulence factors of A. baumannii, specifically focusing on the pathogenic mechanisms of this detrimental pathogen in respiratory infectious diseases. An expansion of the knowledge regarding A. baumannii pathogenesis will contribute to the development of effective therapies based on immunopathology or intracellular signaling pathways to eliminate this harmful pathogen during infections.